A Chronicle of the Soviet Tuva (1950s-1960s) in the Diaries of Salchak Toka - Shirshin, Grygory Ch. (The New Research of Tuva, 2017)
The article examines the diaries of Salchak Kalakbakhorekhovich Toka (1901-1973), a prominent statesman and public figure of the Republic of Tuva, First Secretary of the Central Committee of Tuva People’s Revolutionary Party (1932-1944), First Secretary of Tuva Oblast Committee of the CPSU (1944-1973). Toka’s work as a party official has been covered in detail by historians, both in the Soviet and post-Soviet periods. In 2012, his 110th anniversary was celebrated in the region, and a dedicated research conference was held to honor him.S.K. Toka’s diaries are an invaluable resource for researchers of his life and work after Tuva’s accession to the USSR. Over 20 notebooks with diary entries from 1954 to 1964, written in Russian, were given to the author by Kh.A. Anchima-Toka, S.K. Toka’s widow, and have been preserved by the author, who succeeded S.K. Toka as First Secretary (1973-1991)The diary entries reflect S.K. Toka’s personal workstyle, his methods of management and personal views. The article showcases several diary fragments, including his opinions on people, everyday life in Tuva, its industries, ideological work of the Communist Party, Tuva’s schools and teachers. Also provided are the photocopies of several diary pages, which illustrate both the nature of the entries and the specific features of the diarist’s style.
Keywords: Salchak Kalbakhorekhovich Toka; Tuva; Soviet history; personality in history; diaries; history of Tuva